Mechanical and Electrical Properties Evaluation of Conductive Concrete Matrix - EL Afandi, Mohammed Adnan (2021)
A Master of Science thesis in Civil Engineering by Mohammed Adnan EL Afandi entitled, “Mechanical and Electrical Properties Evaluation of Conductive Concrete Matrix”, submitted in June 2021. Thesis advisor is Dr. Sherif Yehia and thesis co-advisors are Dr. Taha Landolsi and Dr. Nasser Qaddoumi. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).